Assessing the economic value of using structural health monitoring systems on South African bridges by studying the Ermelo-Richards Bay Freight Railway line - Mmekwa, Keamogetswe Antoinette (Structural Engineering and Mechanics Research Group, 2018)
There is a need for appropriate tools and techniques to undertake the vast task of sound repair, maintenance and rehabilitation of concrete infrastructure which is deemed to be deteriorating at unacceptable rates. Low economic growth predictions lead to limited budgets and a deferring of maintenance. The use of technology could be used to extend the useful life of concrete structures. Structural Health Monitoring Systems (SHMS) can be used to monitor structural integrity and the information obtained from these systems can be used in detecting overloading (on bridges for instance) and to alert asset managers of any due maintenance. Büyüköztürk (2007) argues that conventional methods of inspecting the condition of bridges are generally subjective and that this does not give a true reflection of the state of the structure. The objective of this study is to determine the economic value of using SHMS on South African bridges as opposed to conventional bridge inspection methods. The detailed study was conducted on railway bridges on the Transnet Freight Rail (TFR) Ermelo - Richards Bay coal route to assess the contribution that a commodities line such as this one makes to the South African economy. This study makes use of data from Transnet to establish economic value. It is recommended that the results and recommendations be used for a more detailed study into the value of SHMS to be extrapolated for use on other bridges (e.g. road bridges).